Changes in nightmare frequency and nightmare distress after CPAP initiation in patients with obstructive sleep apnea syndrome: an observational study - Schredl, Michael; Lüth, Katharina; Schmitt, Judith (International journal of dream research, 2020)
Nightmare frequency in patients with sleep-related breathing disorders is heightened compared to representative samples. In addition, several studies indicate that nightmares frequency decreases after initiating CPAP treatment. However, data are still scarce. The present study included 19 patients (11 male, 8 female, mean age: 60.53 ± 13.85 yrs.) with sleep-apnea syndrome (mean Respiratory Disturbance Index: 70.08 ± 21.95/hr.) who completed a retrospective eight-point nightmare frequency scale and a five-point nightmare distress scale twice within the context of another study. The first time point was prior to initiating CPAP in the sleep medical center and the second time point after about three to four months (elicited via telephone). Although nightmare distress was lower at t2, nightmare frequency was increased. Despite the limitations, e.g., no information about CPAP compliance, this paradox finding - as nightmare frequency and nightmare distress are inter-related - indicates that sleep-related parameters, e.g., oxygen desaturations, apnea-related arousal, might not explain totally the inter-individual differences in nightmares frequency and nightmare distress in CPAP-treated sleep apnea patients. As a considerable number of patients still suffered from nightmares after CPAP initiation and should receive treatment, further research on nightmares in this patient group seems desirable.